Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1042/bj20061463
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast membranes retard fat digestion and induce satiety: effect of biological membranes on pancreatic lipase/co-lipase

Abstract: Human obesity is a global epidemic, which causes a rapidly increased frequency of diabetes and cardiovascular disease. One reason for obesity is the ready availability of refined food products with high caloric density, an evolutionarily new event, which makes over-consumption of food inevitable. Fat is a food product with high caloric density. The mechanism for regulation of fat intake has therefore been studied to a great extent. Such studies have shown that, as long as fat stays in the intestine, satiety is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
117
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 72 publications
(124 citation statements)
references
References 42 publications
6
117
1
Order By: Relevance
“…In a series of previous studies we have found that thylakoid membranes, the photosynthetic membrane in plant cells, inhibit pancreatic lipase/co-lipase in a dose-dependent way in vitro, an effect confirmed both in animal studies on rat 12 and mice 13 as well as in human studies 14,15 .…”
Section: The Effect Of Thylakoid Isolates On Lipolysis When Included mentioning
confidence: 60%
“…In a series of previous studies we have found that thylakoid membranes, the photosynthetic membrane in plant cells, inhibit pancreatic lipase/co-lipase in a dose-dependent way in vitro, an effect confirmed both in animal studies on rat 12 and mice 13 as well as in human studies 14,15 .…”
Section: The Effect Of Thylakoid Isolates On Lipolysis When Included mentioning
confidence: 60%
“…The thylakoid membranes are negatively charged at neutral pH, with an isoelectric point of 4·7 (27) . Thylakoids expose both hydrophilic and hydrophobic surface groups and have also been found to adsorb onto the surface of oil droplets and form stable oil-in-water emulsions (4,28) . Due to the large size of the thylakoid surface the number of exposed groups per thylakoid particle is large so that, even if the individual group interactions are weak, the sum of them will be large.…”
Section: Discussionmentioning
confidence: 99%
“…The swelling and unfolding may allow the thylakoids to cover a larger surface of the intestine. Native thylakoids have an area of about 2 m 2 /mg chlorophyll (4,15) , and the exposed area may increase significantly upon the unfolding caused by bile salts and fatty acids. It thus appears that this thylakoid network is responsible for the decreased passage through the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations